PENDEKATANKEADILANINTEGRATIF DALAM MEMBANGUNINSTITUSI PUBLIKYANG LEGITIM - Harnowo, Tri; Ali, Alavi (UI Scholars Hub, 2021)
Public institutions have a very important role in providing public services in order to fulfill basic needs and the rights of every citizen, therefore the formation and operation must have public legitimacy. This paper discusses conceptual ideas in establishing legitimate public institutions based on the integrative justice principle, by taking Rawlss proscedural justice, Habermass communication theory and Lind’s perceptive justice as theoritical framework. The results of this study provide a concept of legitimate public institutions where in its formation and operatioan must fulfill the principles of participatory, constitutionality, universality, accessibility, efficiency, partiality, dialectic, deliberative, care, respect and explanatory.